Romanticism and animal rights - Perkins, David, 1928- (Cambridge studies in Romanticism ;, 2003)
In England in the second half of the eighteenth century an unprecedented amount of writing urged kindness to animals: from sermons and encyclopedias to the work of the great Romantic poets. Romanticism and Animal Rights shows how English Romantic writing took up issues of what we now call animal rights.